2021
DOI: 10.16993/sjdr.783
|View full text |Cite
|
Sign up to set email alerts
|

‘In the Next Moment I Answer, it is Not Possible.’ Professionals’ Experiences from Transition Planning for Young People

Abstract: In this article, we explore dilemmas professionals experience in the planning for the transition to adulthood for young people with disabilities. Five group interviews with a total of 16 professionals working in the habilitation services were conducted. They experienced structural shortcomings and a lack of resources to support the aspirations of the young people with disabilities. Much effort was directed towards giving young people a 'realistic' understanding of what they can expect from the public services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Coordinators are often stretched between high demands and limited resources, and struggle to interpret their roles (Tveit & Cameron 2013;Albertini Früh et al 2023). Bekken et al (2021) found that a lack of time and resources requires other professionals in habilitation services to provide users with a 'realistic' understanding of what users can expect from public services. Nevertheless, there is limited knowledge of how the coordinator arrangement is implemented and experienced by parents of disabled children and coordinators in Norway.…”
Section: Coordinators and Welfare Servicesmentioning
confidence: 99%
“…Coordinators are often stretched between high demands and limited resources, and struggle to interpret their roles (Tveit & Cameron 2013;Albertini Früh et al 2023). Bekken et al (2021) found that a lack of time and resources requires other professionals in habilitation services to provide users with a 'realistic' understanding of what users can expect from public services. Nevertheless, there is limited knowledge of how the coordinator arrangement is implemented and experienced by parents of disabled children and coordinators in Norway.…”
Section: Coordinators and Welfare Servicesmentioning
confidence: 99%